Can Met-PET/CT Predict Sporadic Multiglandular Hyperparathyroidism? Report of a Case and Review of the Literature - Andreas Hillenbrand; Johannes Lemke; Doris Henne-Bruns; Ambros J. Beer; Vikas Prasad (Case Reports in Endocrinology)
Background. Primary hyperparathyroidism (pHPT) is a common endocrine disorder of the parathyroid glands. In most cases pHPT is caused by single gland disease, but about 10% of patients suffer from sporadic multiglandular disease (MGD). Patients with MGD, especially with ectopic parathyroid adenomas, have an increased risk for persistence/recurrence after surgery. Normally, sporadic MGD cannot be diagnosed preoperatively by parathyroid scintigraphy. We analyzed the potential of positron emission tomography/computed tomography (Met-PET/CT) to predict MGD. Methods and Case Presentation. We reviewed the literature, if preoperative Met-PET/CT could predict MGD in patients with pHPT. Further, we present a 71-year-old female with ectopic MGD. Preoperative localization via Met-PET/CT showed MGD with two areas suspected to be enlarged parathyroid glands (left lateral to the thyroid lobe and posterior mediastinum). Both diagnostic findings were extirpated and parathormone dropped into normal levels. Results. We identified four additional manuscripts, referring to MGD and Met-PET/CT with divergent results. Preoperative localization diagnostics using Met-PET/CT may not necessarily identify MGD. In most cases, Met-PET/CT localized only one adenoma and localizes larger adenomas more reliably than smaller adenomas. Conclusion. Identifying patients at risk of MGD preoperatively remains challenging. We found MET-PET/CT seems to predict MGD in patients with large size and high weight PTH adenomas. For ectopic parathyroid adenomas, accurate preoperative localization is the key to successful surgical removal. Met-PET/CT appears to have great potential in soft-tissue analysis of complex anatomical regions and can predict ectopic parathyroid adenomas.